Analisis Waktu Menggunakan Microsoft Project Pada Pekerjaan Gedung A1 Pemondokan Upt. Asrama Haji Embarkasi Aceh - Zaiyanna Fitri; Dedek Ariansyah; Heru Pramanda (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
With current technological developments, it affects construction management where computer programs can simplify the process of making reports, activities, controlling, and controlling the activities of a project. The object of this research is the A1 Building for the Hajj Embarkation Dormitory in Aceh, which is located on Teuku Nyak Arief Street, Kuta Alam District, Banda Aceh City. This building project is scheduled for 180 days starting from 05 July 2021-05 December 2021 with a budget of Rp 28,370,150,000.00 (Twenty Eight Billion Three Hundred Seventy Million One Hundred Fifty Thousand Rupiah). an effective and efficient time duration is obtained by reviewing structural work from the 1st, 2nd, 3rd, 4th, and rooftop floors. Primary data obtained are the number of workers. Secondary data is obtained from literature studies and related agencies as build drawing and time schedule. The results of the research are that there is an accelerated time duration for structural work from 91 days to 85 days with an initial work date of 09 August 2021- 07 November 2021 to 09 August 2021-01 November 2021. The benefit of the research is to provide solutions the fastest time by comparing the time schedule obtained from contractors and Microsoft Project 2019 software.